A Digitally Controlled 125 kVdc, 30kW Power Supply with an LCC Resonant Converter Working at Variable DC-link Voltage: Full Scale Prototype Test Results - Gavin, S; Carpita, M; Ecoeur, P; Biner, H.-P; Paolone, M; Louokdom, E.T (7th IET International Conference on Power Electronics, Machines and Drives (PEMD 2014), 2014)
In this paper, a high output voltage power converter working at variable input DC-link voltage is presented. The variable DC link voltage opens to very interesting solution at system level. However, those solutions will be the subject of futures papers. Only the main power converter structure is presented here. After an evaluation of the most promising converter topologies for the required high voltage and power, eventually an LCC resonant converter with phase shift control has been chosen. The resonant converter is followed by a double secondary high frequency transformer with a two diode voltage doublers. The system has been fully analysed from the theoretical point of view, designed, built and tested. The control system has been fully digital implemented making use of a TI DSP microcontroller, TMS320X28335.